2021
DOI: 10.1200/jco.2021.39.15_suppl.e14513
|View full text |Cite
|
Sign up to set email alerts
|

Phase I experience with first in class TnMUC1 targeted chimeric antigen receptor T-cells in patients with advanced TnMUC1 positive solid tumors.

Abstract: e14513 Background: MUC1 is a glycoprotein that is expressed in healthy tissues on the luminal surface of simple and glandular epithelium. In tumors that arise from these cells, an alternate form with aberrant glycosylation is frequently over expressed and distinguishes tumor associated TnMUC1 from normal MUC1. We have generated a novel chimeric antigen receptor (CAR) targeting the TnMUC antigen comprised of a mouse anti-human scFv derived from the monoclonal antibody 5E5 which recognizes the epitope comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In addition, a multi-center first-in-human phase I clinical trial investigated the safety and efficacy of TnMUC1-CAR T-cells with CD2 costimulatory domain in the treatment of 6 patients with TnMUC positive solid tumors including metastatic treatment-resistant ovarian cancer, pancreatic adenocarcinoma, TNBC, or NSCLC. They found that CAR T-cells were expanded in all patients, particularly those who had undergone lymphodepleting chemotherapy with fludarabine and cyclophosphamide, and that the intervention was safe, with no on-target/off-tumor toxicity (NCT04025216) ( 78 ). The efficacy of the treatment is scheduled to be evaluated in a second expansion phase that encompasses 72 more patients.…”
Section: Target Antigens For Car T-cell Therapy Of Solid Tumors In Cl...mentioning
confidence: 99%
“…In addition, a multi-center first-in-human phase I clinical trial investigated the safety and efficacy of TnMUC1-CAR T-cells with CD2 costimulatory domain in the treatment of 6 patients with TnMUC positive solid tumors including metastatic treatment-resistant ovarian cancer, pancreatic adenocarcinoma, TNBC, or NSCLC. They found that CAR T-cells were expanded in all patients, particularly those who had undergone lymphodepleting chemotherapy with fludarabine and cyclophosphamide, and that the intervention was safe, with no on-target/off-tumor toxicity (NCT04025216) ( 78 ). The efficacy of the treatment is scheduled to be evaluated in a second expansion phase that encompasses 72 more patients.…”
Section: Target Antigens For Car T-cell Therapy Of Solid Tumors In Cl...mentioning
confidence: 99%
“…95 Similarly, stable disease (achieved in 3 of 6 treated subjects) was the best response achieved using CAR T-cells specific for the Tn glycoform of MUC1. 105…”
Section: Clinical Experience Of Car T-cell Immunotherapy Of Lung Cancermentioning
confidence: 99%
“…The investigators propose to evaluate safety and preliminary antitumor activity in patients with metastatic MUC1*-positive breast cancer [322]. Moreover, a multicentric clinical trial is evaluating a CART-TnMUC1 immunotherapy in solid tumors (triple-negative breast cancer, epithelial ovarian cancer, pancreatic cancer, and non-small cell lung cancer) and TnMUC1 positive multiple myeloma, designed to identify the dose and regimen at which CART-TnMUC1 cells can be safely administered intravenously following lymphodepletion (NCT04025216) [330]. In a second expansion phase enrolling 72 more patients, efficacy is due to be assessed.…”
Section: Car-t Cells Targeting Gd2mentioning
confidence: 99%